Animal Models of Vestibular Evoked Myogenic Potentials: The Past, Present, and Future - Corneil, Brian D.; Camp, Aaron J. (Frontiers in Neurology, 2018)
Vestibular-evoked myogenic potentials (VEMPs) provide a simple and cost-effective means to assess the patency of vestibular reflexes. VEMP testing constitutes a core screening method in a clinical battery that probes vestibular function. The confidence one has in interpreting the results arising from VEMP testing is linked to a fundamental understanding of the underlying functional anatomy and physiology. In this review, we will summarize the key role that studies across a range of animal models have fulfilled in contributing to this understanding, covering key findings regarding the mechanisms of excitation in the sensory periphery, the processing of sensory information in central networks, and the distribution of reflexive output to the motor periphery. Although VEMPs are often touted for their simplicity, work in animals models have emphasized how vestibular reflexes operate within a broader behavioral and functional context, and as such vestibular reflexes are influenced by multisensory integration, governed by task demands, and follow principles of muscle recruitment. We will conclude with considerations of future questions, and the ways in which studies in current and emerging animal models can contribute to further use and refinement of this test for both basic and clinical research purposes.